Importance of ABCC1 for cancer therapy and prognosis. (August 2014) - Kunická, Tereza; Souček, Pavel
Abstract Multidrug resistance presents one of the most important causes of cancer treatment failure. Numerous in vitro and in vivo data have made it clear that multidrug resistance is frequently caused by enhanced expression of ATP-binding cassette (ABC) transporters. ABC transporters are membrane-bound proteins involved in cellular defense mechanisms, namely, in outward transport of xenobiotics and physiological substrates. Their function thus prevents toxicity as carcinogenesis on one hand but may contribute to the resistance of tumor cells to a number of drugs including chemotherapeutics on the other. Within 48 members of the human ABC superfamily there are several multidrug resistance-associated transporters. Due to the well documented susceptibility of numerous drugs to efflux via ABC transporters it is highly desirable to assess the status of ABC transporters for individualization of treatment by their substrates. The multidrug resistance associated protein 1 (MRP1) encoded by ABCC1 gene is one of the most studied ABC transporters. Despite the fact that its structure and functions have already been explored in detail, there are significant gaps in knowledge which preclude clinical applications. Tissue-specific patterns of expression and broad genetic variability make ABCC1/MRP1 an optimal candidate for use as a marker or member of multi-marker panel for prediction of chemotherapy resistance. The purpose of this review was to summarize investigations about associations of gene and protein expression and genetic variability with prognosis and therapy outcome of major cancers. Major advances in the knowledge have been identified and future research directions are highlighted.